'Raji': language of a vanishing Himalayan tribe - Rastogi, Kavita (2024)
Language is a repository for the culture and worldview of its speakers. Its grammar and lexicon store the shared experiences of past generations, and a language is the channel by which knowledge and beliefs of one generation are transmitted to the next. It confers a sense of identity upon its native speakers. Today there are at least 6000 living languages across the world. Of them, 330 languages have more than one million speakers each and there are 51 languages that have only one speaker each. David Crystal (2000) believes that only 4% of the languages in the world are spoken by 96% of the total world population and conversely, only 4% people speak the remaining 96% of the world languages. Gradually these 96% of the world's languages are shifting, decaying, or dying out. It must be understood that with the disappearance of any language minor or major, not only the language, is lost but also its cultural heritage and its worldview. By allowing languages to die out we are destroying what deserves to be preserved.